PENGARUH PELAYANAN JASA PUSKESMAS TERHADAP KEPUASAN PASIEN DI PUSKESMAS SIWULUH KABUPATEN BREBES - Apriyani, Apriyani; Absor, Ulul; Handayani, Sri Ratih (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2024)
ABSTRACTThis research is entitled The Influence of the Quality of Community Health CenterServices on Patient Satisfaction at the Siwuluh Community Health Center, BrebesRegency. The objectives to be achieved in this research are:1. To find out whether the quality of community health center services has a significant influence on patient satisfaction.2. To find out how much influence the quality of puskesmas services has on patientsatisfaction Meanwhile, the hypothesis proposed is:1. That the influence of the quality of community health center services on patientsatisfaction at the Siwuluh Community Health Center in Brebes Regency is significant.2. The influence of the quality of community health center services on patient satisfaction at the Siwuluh Community Health Center in Brebes Regency is large and positive. The research method used was a case study at the Siwuluh Community Health Center, Bulakamba District, Brebes Regency, while the data collection methods used were surveys, interviews, questionnaires and library research. In testing the hypothesis, a simple regression coefficient analysis tool was used with the t and F tests. From the results of the analysis, conclusions can be drawn: 1. There is a significant influence between service quality and patient satisfaction.Based on the statistical analysis of the F test, using a confidence level of 95% (α = 0.05) and degree of freedom (df) = (k – 1) and (n – k – 1), the F table is 2.71, while the calculation results What was done resulted in an F count of 954.093. Because Fcount is greater than Ftable, the Ho hypothesis is rejected, and the t test. By using a confidence level of 95% (α = 0.05) and degree of freedom (df) = k and (n – k – 1), the ttable is 1.6609. From the calculations carried out, the service quality tcount value is 30.888, because tcount is greater than ttable (30.888 > 1.6609), then partially the service quality variable has a significant influence on patient satisfaction. Thus, the first hypothesis which states that the service quality variable (X) has a significant influence on patient satisfaction is accepted.2. From the results of simple linear regression calculations, it is obtained that Y =1.012 + 0.982 This means that patients still have satisfaction with treatment without any change in the service quality variable, and if the service quality variable (X) increases by one unit, it will increase patient satisfaction (Y) by 98.2 units. The strength of this influence can be seen from the coefficient of determination of 90.7%, which means that variations in the ups and downs of patient satisfaction are influenced by service quality by 90.7%, while the remaining 9.3% is influenced by other factors not examined in this research.